Do trade‐offs govern plant species' responses to different global change treatments?. Issue 6 (17th April 2022) - Langley, J. Adam; Grman, Emily; Wilcox, Kevin R.; Avolio, Meghan L.; Komatsu, Kimberly J.; Collins, Scott L.; Koerner, Sally E.; Smith, Melinda D.; Baldwin, Andrew H.; Bowman, William; Chiariello, Nona; Eskelinen, Anu; et al.
Abstract: Plants are subject to trade‐offs among growth strategies such that adaptations for optimal growth in one condition can preclude optimal growth in another. Thus, we predicted that a plant species that responds positively to one global change treatment would be less likely than average to respond positively to another treatment, particularly for pairs of treatments that favor distinct traits. We examined plant species' abundances in 39 global change experiments manipulating two or more of the following: CO2, nitrogen, phosphorus, water, temperature, or disturbance. Overall, the directional response of a species to one treatment was 13% more likely than expected to oppose its response to a another single‐factor treatment. This tendency was detectable across the global data set, but held little predictive power for individual treatment combinations or within individual experiments. Although trade‐offs in the ability to respond to different global change treatments exert discernible global effects, other forces obscure their influence in local communities.